The separation of trypanosomes from blood by anion exchange chromatography: From Sheila Lanham's discovery 50 years ago to a gold standard for sleeping sickness diagnosis. - Veerle Lejon; Philippe Büscher; Romaric Nzoumbou-Boko; Géraldine Bossard; Vincent Jamonneau; Bruno Bucheton; Philippe Truc; Jean-Loup Lemesre; Philippe Solano; Philippe Vincendeau (Public Library of Science (PLoS), 2019)
Human African trypanosomiasis (HAT), or sleeping sickness, is a neglected tropical disease that is fatal if untreated, caused by Trypanosoma brucei gambiense and T. brucei rhodesiense. In its 2012 roadmap, WHO targeted HAT for elimination as a public health problem in 2020 and for zero transmission in 2030. Diagnosis of HAT is a multistep procedure comprising of clinical suspicion, confirmation, and stage determination. Suspects are identified on clinical signs and/or on screening for specific antibodies. Parasitological confirmation of suspects remains mandatory to avoid unnecessary toxic drug administration. The positive predictive value of the antibody detection tests is low. Simple parasite detection techniques, microscopic examination of lymph node aspirate, or stained thick blood films lack sensitivity, whereas in T. brucei gambiense patients, the number of blood trypanosomes may be very low. Parasite concentration techniques are therefore indispensable. Half a century ago, Sheila Lanham discovered a technique to separate trypanosomes from the blood of infected rodents, based on anion exchange chromatography with diethyl amino ethyl (DEAE) cellulose, a weak anion exchanger. Between pH 6-9, trypanosome surface is less negatively charged than that of blood cells. When blood is poured on top of a DEAE cellulose column, blood cells are retained, whereas parasites pass the column together with the elution buffer. The result is a pure suspension of trypanosomes that retain their morphology and infectivity. Because cell surface charges vary among trypanosome and mammal species, the optimal buffer pH and ionic strength conditions for different combinations of host and trypanosome species were established. Lanham's technique revolutionized the diagnosis of HAT. It is indispensable in the production of the Card Agglutination Test for Trypanosomiasis (CATT), the most used field test for screening in T. brucei gambiense HAT foci and essential to confirm the diagnosis in suspected people. Lumsden and colleagues developed the mini anion exchange centrifugation technique (mAECT). After adaptation for field conditions, its superior diagnostic and analytical sensitivity compared to another concentration technique was demonstrated. It was recommended as the most sensitive test for demonstrating trypanosomes in human blood. At the beginning of the 21st century, the mAECT was redesigned, allowing examination of a larger volume of blood, up to 0.35 ml with whole blood and up to 10 ml with buffy coat. The plastic collector tube in the new kit is also used for detection of trypanosomes in the cerebrospinal fluid. Unfortunately, mAECT also has some disadvantages, including its price, the need to centrifuge the collector tube, and the fact that it is manufactured on a noncommercial basis at only two research institutes. In conclusion, 50 years after Sheila Lanham's discovery, CATT and mAECT have become essential elements in the elimination of HAT.